Determination of Nucleotide Sequences of Mitochondrial Plasmid pGT704 of Paramecium caudatum - T.E. Tallei; M.R. Moeis; H. Endoh; W. Utama (IPTEK The Journal for Technology and Science, 2008)
Many kinds of linear plasmids, or plasmid-like DNAs, in mitochondria have been reported in higher plants and fungi. Nevertheless, such plasmids were not previously known from the animal kingdom. Paramecium is the first example in which a mitochondrial plasmid-like DNA so far discovered among ciliates. In natural stocks, P. caudatum has one of three types of DNA : type I (6.4 kb), type II, a set of four DNAs (8.2 kb; 4.1 kb; 2.8kb; and 1.4 kb) and type III (8.6 kb). Paramecium caudatum stock GT704 only has type-II DNA. The 8.2 and 2.8 kb DNAs are dimers of the 4.1 and 1.4 kb DNA, respectively. The aim of this study was to determine the sequence of mitochondrial plasmid-like DNA in P. caudatum stock GT704 in order to identify potential gene products and other nucleotide sequences that might have relationship with integration of DNA and also the maintanance of DNA itself in mitochondria. The methods used in this study were isolation of the DNA, cloning and sequencing then followed by analysis of sequences obtained using available public domain. The dimers were found to be easily dissociated to monomers when treated with heat underconditions of low ionic strength. These results suggest that each monomer has a sticky end of single- stranded DNA that has complementary nucleotide sequences, and so attaches to each other at the end by base-pairing to form a dimer, leaving a nick that can be filled by ligation using ligase. Nucleotide sequences of some part of the DNA have been obtained randomly. Sequence analysis suggests that these dimers DNAs have 2 ORFs that code for putative RNA and DNA polymerases. It is assumed that the origin of this mitochondrial plasmid-like DNA is transposable element or some viruses since the motif EVI-1 (ectopic viral integration site-1) was found in the sequence. It is also assumed that this DNA can integrate into mtDNA since it also has some sequences homolog to the sequences of mt- DNA of some ciliates.